Analisis Faktor yang Mempengaruhi Penerimaan Nasabah terhadap Layanan Mobile Banking - Hasbi Assidiki Mauluddi (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2020)
The purpose of this study is to investigate factors affecting the consumers intention to use Mobile Banking. A survey was used to collect data from 86 samples from all smartphone device owners and has been experienced with Mobile Banking applications. The proposed Mobile Banking implementation Model In this study is based on the Technology Acceptance Model (TAM) and mobile service Quality (MSQ). Structural Equation Modeling (SEM) is used to analyze data. The results reveal that the ease of use, usability and quality of service to the use of Mobile Banking positively influential. Therefore, the Bank should emphasize the strategy to increase the benefits of Mobile Banking perception by prioritizing this factor into decision making.